2014
DOI: 10.1152/jn.00145.2014
|View full text |Cite
|
Sign up to set email alerts
|

Reach target selection in humans using ambiguous decision cues containing variable amounts of conflicting sensory evidence supporting each target choice

Abstract: Coallier É, Kalaska JF. Reach target selection in humans using ambiguous decision cues containing variable amounts of conflicting sensory evidence supporting each target choice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(31 citation statements)
references
References 79 publications
1
29
0
Order By: Relevance
“…However, as discussed in the previous paragraph, several studies using high-contrast stimuli found longer non-decision times when different aspects of the stimulus were relevant for the task or when the stimuli were more ambiguous (Coallier and Kalaska 2014;Ratcliff and Frank 2012;Ratcliff and Smith 2010).…”
Section: Stimulus Contrast Vs Extraction Of Task-relevant Informationmentioning
confidence: 90%
See 2 more Smart Citations
“…However, as discussed in the previous paragraph, several studies using high-contrast stimuli found longer non-decision times when different aspects of the stimulus were relevant for the task or when the stimuli were more ambiguous (Coallier and Kalaska 2014;Ratcliff and Frank 2012;Ratcliff and Smith 2010).…”
Section: Stimulus Contrast Vs Extraction Of Task-relevant Informationmentioning
confidence: 90%
“…Ratcliff and Smith argued that the relevant information for the brightness discrimination task is immediately apparent and does not require detailed extraction. A recent study by Coallier and Kalaska can be used to further test this hypothesis (Coallier and Kalaska 2014). In their task, subjects viewed a fine-grained checkerboard pattern with randomly distributed red, blue, and yellow squares.…”
Section: Psychophysical Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…The average RT offset of 20–30 ms is not surprising since instructed trials always provided instantaneous and unambiguous evidence whereas choice trials provided rule-neutral evidence. Higher RTs for choice compared to instruction could be due to: (1) a slower drift rate due to absence of clear evidence in the choice case (Roitman and Shadlen, 2002 ; Hanks et al, 2015 ); (2) higher decision thresholds in the case of symmetric reward choice (Cavanaugh et al, 2006 ; Cavanagh et al, 2011 ; Summerfield and Tsetsos, 2012 ); (3) an increased duration of non-decision time, which delays migration initiation, due to unclear stimuli (Mulder and van Maanen, 2013 ; Coallier and Kalaska, 2014 ); or some combination of these possibilities. Only processes that occur with or after the rule-cue can account for differences between instructed and choice trials since subjects were unaware of the trial type prior to the rule-cue.…”
Section: Discussionmentioning
confidence: 99%
“…Which mechanism is responsible for RT reduction and CP increase in which behavioral context is a topic of ongoing research (Summerfield and Tsetsos, 2012 ). In the context of perceptual decision-making, previous studies showed that prior probability adapts migration distance (Bogacz et al, 2006 ; Simen et al, 2009 ; Mulder et al, 2012 ) while strength of evidence steers drift rate (Roitman and Shadlen, 2002 ; Coallier and Kalaska, 2014 ; Coallier et al, 2015 ; Hanks et al, 2015 ). However, the effect of expected value as been accounted for by different explanations: baseline shift (Maddox, 2002 ; Bogacz et al, 2006 ; Mulder et al, 2012 ) or drift rate change (Diederich and Busemeyer, 2006 ).…”
Section: Introductionmentioning
confidence: 99%